Achieving reduced radiation exposure with maintained fluoroscopy effectiveness using ultralow‐dose settings in cryoballoon ablation - Takashi Kaneshiro; Sadahiro Murota; Takeshi Nehashi; Minoru Nodera; Shinya Yamada; Masamitsu Ikeda; Yasuchika Takeishi (Journal of Arrhythmia)
Abstract Background and Aims Optimization of fluoroscopic image quality for reducing radiation exposure in cryoballoon pulmonary vein isolation (CB‐PVI) has not yet been fully investigated. Therefore, we tried to compare the radiation doses among three different X‐ray system settings. Methods Consecutive 148 patients scheduled for their first CB‐PVI were prospectively enrolled: low dose with the use of an anti‐scatter grid for the first 51 patients (LD + G group), low dose without an anti‐scatter grid for the subsequent 46 patients (LD‐G group), and ultralow dose (ULD group) with an anti‐scatter grid for the remaining 51 patients. We compared the radiation doses required to complete CB‐PVI procedures among the groups. There were 27 patients for whom CB‐PVI was performed without cine acquisition, but with fluoroscopy only, and the radiation doses were also compared. Results The median procedure time and fluoroscopy time were 119 and 35.5 min, respectively, with no significant differences among the groups. The median cumulative air Kerma (AK) decreased in both the LD‐G group (71.8 mGy, p < .001) and the ULD group (73.0 mGy, p < .001), compared to the LD + G group (145.0 mGy). Among 27 patients who underwent CB‐PVI without cine acquisition, the median cumulative AK further decreased in both the LD‐G group (31.4 mGy, p < .05) and the ULD group (22.7 mGy, p < .01), compared to the LD + G group (64.6 mGy). Conclusion Using an ULD X‐ray setting and avoiding cine acquisition, we can reduce radiation exposure, while ensuring the necessary fluoroscopy time for the CB‐PVI procedure.